Demand for weather hedges in India: An empirical exploration of theoretical predictions - Hill, Ruth Vargas; Robles, Miguel; Ceballos, Francisco (International Food Policy Research Institute, 2013)
This paper analyzes the demand for rainfall-based weather hedges among farmers in rural India. We explore the predictions of a standard expected utility theory framework on the nature of demand for such products, in particular testing whether demand behaves as predicted with respect to price, the basis of the hedge, and risk aversion using data from a randomized control trial in which price and basis risk was varied for a series of hedging products offered to farmers. We find that demand behaves as predicted, with demand falling with price and basis risk, and appearing hump-shaped in risk aversion. Second, we analyze understanding of and demand for hedging products over time, examining the impact of increased investments in training on hedging products as well as evidence for learning by doing among farmers. We find evidence that suggests that learning by doing is more effective at increasing both understanding and demand.